Marketing Analysis of Bitti Wood (Vitex cofassus) in Bulukumba District, South Sulawesi - Nur Hayati; Achmad Rizal Hak Bisjoe; Abdul Kadir Wakka (Buletin Eboni, 2019)
Bitti wood (Vitex cofassus) harvested from the private forest has a considerable potential to be developed to fulfill the demand of the local and industrial markets, such as to support the Phinisi boat industries. One important factor in supporting the development and utilization of the bitti’s private timber is its marketing system. This study aimeds to describe the profile of bitti wood marketing and analyze it in supporting the Phinisi boat industries in Bulukumba district. Data collection was carried out through observation and interview several parties involved in the marketing process of bitti by using an interview guide (questionnaire). The results showed that bitti wood marketing actors in Bulukumba District included farmers, middlemen, and the Phinisi industries. There were two patterns of bitti wood marketing at the study site, i.e. the pattern I: Farmers à Phinisi industries and pattern II: Farmers à Middlemen àPhinisi industries. The lowest profit share was received by bitti farmers in the pattern I was about 31,6% and pattern II was about 29,5%, which does not fairly reflect their contribution. To maintain the sustainability of bitti private timber, there is a need to develop a more efficient bitti marketing process from upstream to downstream.